O3-S1.01 British Ocular Syphilis Study (BOSS): National Surveillance Study of intraocular inflammation secondary to infectious syphilis. (10th July 2011) - Goh, B; Matthew, R; Simms, I; Westcott, M
Abstract : Background: Syphilis poses a significant public health problem. There has been a 1032% increase in the incidence of syphilis between 1999 and 2008 in the UK. There are currently no epidemiological studies looking at the incidence of ocular syphilis in the light of the outbreak. Ocular syphilis is a rare, but treatable if recognised early. The purpose of this study is to ascertain the incidence of intraocular syphilis in the UK and to characterise the clinical presentation patterns of ocular syphilis. Methods: A prospective study was conducted in the UK and Republic of Ireland, where cases of ocular syphilis were reported through the national reporting system (British Ocular Surveillance Unit) over an 18-month period from May 2009. Case definition was any adult patient who presented with intraocular inflammation and early infectious syphilis as evidenced by positive syphilis serology with (1) high titre RPR of >1:8 or (2) signs of secondary syphilis. Results: 35 new cases of ocular syphilis were reported (annual incidence 0.46 per million) with a mean age of 51.5 years (range 22–75 years). 86% were males; 88% were caucasians and 12% were Afro-Caribbean. The mean duration of symptoms was 1.0 month prior to presentation (range 2 days to 4 months). 46% of patients had bilateral involvement and the mean presenting logMAR visual acuity was 0.48 (20/60 Snellen; range −0.1–1.86). 54% had visual acuities of 20/40 Snellen or better at initial consultation. Presenting acuity was not influenced by duration of visual symptoms. Intraocular pressure on presentation was elevated in only one patient (27 mm Hg). Although 68.4% had an anterior uveitis (AU), isolated AU was rare (1 case). 63% had vitritis; 61% had a form of posterior uveitis, (60% retinitis, 56% vasculitis, 50% macular oedema, 28% choroiditis). 32% of cases had optic nerve involvement. Of males whose sexual orientation was ascertained 85% were MSM. Of patients whose HIV status was known, 71% were HIV positive. Conclusions: This study is the largest prospective series of ocular syphilis in the post-penicillin era providing up to date Western European incidence, demographic and clinical data. Syphilitic uveitis affects mainly adult males of all ages; majority were MSM or HIV positive. The uveitis is normotensive, posterior uveitis is common, and AU rarely presents in isolation. Clinician and public health awareness of ocular syphilis remains important.